1984
DOI: 10.1088/0031-9155/29/4/003
|View full text |Cite
|
Sign up to set email alerts
|

Noise and contrast detection in computed tomography images

Abstract: A discrete representation of the reconstruction process is used in an analysis of noise in computed tomography (CT) images. This model is consistent with the method of data collection in actual machines. An expression is derived which predicts the variance on the measured linear attenuation coefficient of a single pixel in an image. The dependence of the variance on various CT scanner design parameters such as pixel size, slice width, scan time, number of detectors, etc., is then described. The variation of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
31
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 12 publications
(5 reference statements)
4
31
0
Order By: Relevance
“…The dose is a function of the energy deposited through photon absorption and energy loss via Compton scattering interactions. The smaller voxels of micro-CT (relative to clinical CT) require much higher dose, since any voxel – independent of its size – needs to interact with a certain number of x-ray photons for adequate image quality (Faulkner and Moores, 1984; Brooks and Di Chiro, 1976). Therefore, in order to compensate for the reduction of the voxel size, the photon fluence must be much larger in micro-CT to achieve a signal-to-noise ratio comparable to clinical CT.…”
Section: Micro-ct: Design and Performancementioning
confidence: 99%
“…The dose is a function of the energy deposited through photon absorption and energy loss via Compton scattering interactions. The smaller voxels of micro-CT (relative to clinical CT) require much higher dose, since any voxel – independent of its size – needs to interact with a certain number of x-ray photons for adequate image quality (Faulkner and Moores, 1984; Brooks and Di Chiro, 1976). Therefore, in order to compensate for the reduction of the voxel size, the photon fluence must be much larger in micro-CT to achieve a signal-to-noise ratio comparable to clinical CT.…”
Section: Micro-ct: Design and Performancementioning
confidence: 99%
“…In particular, acquiring CT images of the animal heart with organ definition and temporal resolution comparable to that in humans requires ~10-fold improvement in temporal resolution, and ~100-fold increment in spatial resolution. On the other hand, the high spatial resolution requires much higher dose relative to clinical CT, because any voxel must interact with a decent number of x-ray photons for adequate image quality (Faulkner and Moores, 1984, Brooks and Chiro, 1976). Therefore, to compensate for the reduction in focal spot and image voxel size, the detector integration time and scanning speed have become too long to be practical in many important scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Limiting the scope to CT, Riederer et al [27] derived an analytical CT NPS formalism and showed it to be proportional to the squared transfer function of the reconstruction filter. Furthermore, Wagner et al [28], [29], Hanson [30], and Faulkner and Moores [31] connected the analytical NPS to NEQ and applied the NEQ to simple detection tasks. On the other hand, Kijewski and Judy [32] showed an asymmetric CT NPS due to aliasing using a discrete analysis.…”
mentioning
confidence: 99%